2016
DOI: 10.1177/0962280216642264
|View full text |Cite
|
Sign up to set email alerts
|

Assessing methods for dealing with treatment switching in clinical trials: A follow-up simulation study

Abstract: When patients randomised to the control group of a randomised controlled trial are allowed to switch onto the experimental treatment, intention-to-treat analyses of the treatment effect are confounded because the separation of randomised groups is lost. Previous research has investigated statistical methods that aim to estimate the treatment effect that would have been observed had this treatment switching not occurred and has demonstrated their performance in a limited set of scenarios. Here, we investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 37 publications
2
67
1
Order By: Relevance
“…For this reason, other adjustment methods may be preferable in trials with high switching proportions. 1,10,12…”
Section: Inverse Probability Of Censoring Weightsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, other adjustment methods may be preferable in trials with high switching proportions. 1,10,12…”
Section: Inverse Probability Of Censoring Weightsmentioning
confidence: 99%
“…Simulation studies have shown that these methods tend to produce more accurate estimates of the switching-adjusted estimand than simple adjustment methods or a standard intention to treat (ITT) analysis, but their performance can be compromised when underlying assumptions are violated. [10][11][12] Analyses using more rigorous adjustment methods are regularly submitted to HTA agencies, in some cases providing enough evidence to alter reimbursement decisions. In the case of sunitinib versus best supportive care for the treatment of gastrointestinal stromal tumors, for example, the incremental cost-effectiveness ratio per quality-adjusted life-year changed from ÂŁ90500 in an ITT analysis to ÂŁ31800 with the RSPFTM; this led to sunitinib being recommended for reimbursement by the National Institute for Health and Care Excellence (NICE).…”
Section: Introductionmentioning
confidence: 99%
“…It is also not possible to allow for time-dependent treatment effects. Other advantages and disadvantages of these methods have been discussed more fully elsewhere [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…In common with previous simulation studies, 13,26 we simulated datasets with a sample size of 500 and 2:1 randomisation in favour of the experimental group, and with treatment switching permitted from the control group onto the experimental treatment. A step-by-step description of our data generating mechanism is provided in online Appendix A.…”
Section: Data Generating Mechanismmentioning
confidence: 99%